A experiência do inconsciente para o psicanalista em formação, segundo Freud - Vieira, Marcus Kleredis Monteiro (2010)
This research aims at following the development of Freudian propositions referring to the experience with the unconscious - self-analysis, mutual interpretation and personal analysis – for the analytic training. Having this as a focus, it starts with a biographical examination of clinical, theoretical and institutional aspects of the training analysis by three authors: Ferenczi, Balint and Lacan. After establishing the problem upon the perspectives propounded by those three authors, a research of Freud’s related texts was carried out. Freud’s approach in developing the issue was, therefore, divided into three distinct moments: 1) The process of self-analysis as a starting point for later Freudian postulations; 2) First analysis recommendations for the beginning psychoanalyst going from the functioning of the “Wednesday Group” up to article titled On the Teaching of Psychoanalysis in the University (1919); 3) Formulations following the creation of the formation system for psychoanalysts of The Berlin Psychoanalytic Institute issued according to theoretical paradigms from the second topic. On a first moment, upon developing the issue as propounded by Freud, it was observed changes related to the role of self-analysis that starts with the doubtful method of treatment and little by little develops into a privileged form of accessing phenomena that supports Freudian formulations about the unconscious. On a second moment, it was investigated the issue of the experience with the unconscious according to its articulation with developments from the psychoanalytical movement going from the “Wednesday Group” period up to the time preceding creation of the first system for the formation of psychoanalysts. It was finally investigated the Freudian development of the issue concerning the experience of the unconscious for the beginning psychoanalyst from the advent of the second topic and the concept of death drive. In concluding it was presented the researcher’s contributions to the discussion related to the experience of the unconscious - self-analysis, mutual interpretation and personal analysis – and, in a general approach, to the formation of psychoanalysts.